Solid Lipid Nanoparticles (SLN): Method, Characterization and Applications - Garud, Akanksha; Singh, Deepti; Garud, Navneet (International Current Pharmaceutical Journal, 2012)
Solid lipid nanoparticles (SLN) have emerged as a next-generation drug delivery system with potential applications in pharmaceutical field, cosmetics, research, clinical medicine and other allied sciences. Recently, increasing attention has been focused on these SLN as colloidal drug carriers for incorporating hydrophilic or lipophilic drugs. Proteins and antigens intended for therapeutic purposes may be incorporated or adsorbed onto SLN, and further administered by parenteral routes or be alternative routes such as oral, nasal and pulmonary. The obstacles associated with conventional chemotherapy may be partially overcome by encapsulating them as SLN. The present review focuses on the utility of SLN in terms of their advantages, production methodology, characterization and applications. If properly investigated, SLNs may open new vistas in therapy of complex diseases. DOI: http://dx.doi.org/10.3329/icpj.v1i11.12065 International Current Pharmaceutical Journal 2012, 1(11): 384-393